TOXICOLOGICAL EVALUATION OF 1.1.3-TRICHLORO-3-PHENYLPROPANE AS A RISK FACTOR FOR WORKERS’ HEALTH - Нина Андреевна Мартынова; Лариса Геннадьевна Горохова; Галина Михайловна Шавцова (Медицина в Кузбассе, 2017)
Subject. The toxic properties of 1.1.3-trichloro-3-phenylpropane (ChPhP).